2018
DOI: 10.31111/palaeobotany/2018.9.54
|View full text |Cite
|
Sign up to set email alerts
|

Fossil evidence of initial radiation of Cercidiphyllaceae

Abstract: Cercidiphyllaceae-like leaves and fruits from the Lower Cretaceous deposits of Northeastern Asia were restudied. In the result one species of Jenkinsella fruits and five species of Trochodendroides leaves were recognized, including Trochodendroides potomacensis (Ward) Bell, T. buorensis Golovneva, T. sittensis Golovneva, sp. nov., T. vachrameeviana (Iljinskaja) Golovneva, comb. nov., and T. denticulata (Budantsev et Kiritchkova) Golovneva, comb. nov. Two new combinations and one new species are published. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…3) showed that all three of the WCS monotypic families (i.e., Altingiaceae, Cercidiphyllaceae, and Daphniphyllaceae) are [59,62]. Within Cercidiphyllaceae, four extinct genera (Jenkinsella, Joffrea, Nyssidium, and Trochodendroides) have been reported [63][64][65][66]. Among them, a Joffrea species has been documented from the late Paleocene of Canada [64]; 10 Jenkinsella, 13 Nyssidium, and 60 Trochodendroides species [67,68] have been discovered across the Northern Hemisphere spanning from early Cretaceous Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) showed that all three of the WCS monotypic families (i.e., Altingiaceae, Cercidiphyllaceae, and Daphniphyllaceae) are [59,62]. Within Cercidiphyllaceae, four extinct genera (Jenkinsella, Joffrea, Nyssidium, and Trochodendroides) have been reported [63][64][65][66]. Among them, a Joffrea species has been documented from the late Paleocene of Canada [64]; 10 Jenkinsella, 13 Nyssidium, and 60 Trochodendroides species [67,68] have been discovered across the Northern Hemisphere spanning from early Cretaceous Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to the most recent time-calibrated angiosperm phylogeny [29], the stem age of the WCS is constrained to 105.2 Ma. In addition, the earliest fossils of the extinct genera Trochodendroides [66], Allonia/Androdecidua [60,62], and Archamamelis [59,61,62] were chosen to constrain the stem ages of Cercidiphyllaceae (100.5 Ma), Loropetaleae (83.6 Ma), and Hamamelideae (83.6 Ma), respectively. These fossils are either infructescences/fruits or well-preserved flowers with pollen [60,61,66], and their systematic positions have been robustly verified and extensively used for calibrating the phylogeny of angiosperms [e.g., 29,62,105].…”
Section: Fossil Record and Estimation Of Divergence Timementioning
confidence: 99%
“…However, during the Late Cretaceous, Trochodendroides-Jenkinsella-Alasia fossils were widespread in middle and high latitudes of the Northern Hemisphere. In the lowermiddle Albian deposits of Northeastern Asia, they are represented by one species of Jenkinsella fruits and five species of Trochodendroides leaves from different localities (Golovneva and Zolina 2018). These fossils reflect the early history of Cercidiphyllaceae or its ancestors.…”
Section: Systematic Affinitymentioning
confidence: 99%
“…This leaf is very similar to leaves of Trochodendroides sittensis Golovn. from earlymiddle Albian Khatyryk Formation of the Lena River basin, Yakutia, Russia (Golovneva and Zolina 2018).…”
Section: Early-middle Albian Razdolnaya Coal Basin Galenki Formationmentioning
confidence: 99%
See 1 more Smart Citation